Tailoring atomically dispersed cobalt–nitrogen active sites in wrinkled carbon nanosheets via "fence" isolation for highly sensitive detection of hydrogen peroxide. Issue 6 (18th January 2022) - Hu, Yue; Bai, Chen; Li, Meng; Hojamberdiev, Mirabbos; Geng, Dongsheng; Li, Xiaoguang
Abstract : Wrinkled CNSs with abundant mesopores, high N-doping, and atomically dispersed Co–N x active sites through "fence" isolation enable efficient H2 O2 detection. Abstract : Stable and highly sensitive determination of hydrogen peroxide (H2 O2 ) is needed in various fields ranging from disease prevention to environmental protection. The construction of inexpensive and highly active transition-metal-based nitrogen-doped carbon (TM-N/C) electrocatalysts is a promising strategy for highly sensitive enzyme-free electrochemical detection of H2 O2 . Deriving the TM-N/C electrocatalysts with abundant active sites and uniform micro/mesopores from rationally designed metal–organic frameworks (MOFs) as self-sacrificing templates has been demonstrated as one of the most effective ways. However, the phenomenon of spontaneous aggregation of metal atoms often occurs in the synthesis of TM-N/C electrocatalysts, which reduces the density of the TM-N moieties and destroys the original active sites in the catalyst. For converting the metal atoms in the precursor directly into TM-N atomically active moieties, we present a straightforward approach, which is based on the pyrolysis of a complex of nanosized Zn/Co bimetallic ZIF crystals (0–8% Co) and carbon nitride (g-C3 N4 ). This approach enables the controllable synthesis of nitrogen-doped carbon nanosheets anchored with atomically dispersed cobalt–nitrogen active sites (Co–N/CNSs). Particularly, the Co (4%)–N/CNS synthesized using Zn/Co ZIF (4% Co) and g-C3 N4 precursors possesses a maximized Co atom utilization and favorable degree of graphitization. The Co (4%)–N/CNS exhibits excellent sensing performance towards H2 O2 reduction with a wide linear current response ranging from 1 × 10 −6 to 0.5 × 10 −3 M and from 0.5 × 10 −3 to 1 × 10 −1 M, high sensitivity of 468.95 and 605.50 μA mM −1 cm −2, a low detection limit of 6.18 × 10 −9 M, and good anti-interference, stability, and reproducibility. Hence, the Co (4%)–N/CNS has practical application potential for precisely detecting the concentration of H2 O2 at a trace level.